2017
DOI: 10.1016/j.jand.2017.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Snacking and Diet Quality Are Associated With the Coping Strategies Used By a Socioeconomically Diverse Urban Cohort of African-American and White Adults

Abstract: Background Stress affects health-related quality of life through several pathways including physiological processes and health behaviors. There is always a relationship between stress, the stimulus, and coping, the response. The relationship of snacking and snackers’ diet quality, to stress-coping is a topic overlooked in research. Objectives The study was primarily designed to determine whether energy provided by snacks and diet quality were associated with coping behaviors to manage stress. Design Baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…To our knowledge, there is no data available assessing the association between optimism and snacking behavior. Snacking has been associated with depressive symptomatology [65], perceived stress [66] and coping strategies [67]. We can hypothesize that the better coping strategies observed in more optimistic individuals [29] lead to lower psychological distress [68,69], which can in turn decrease snacking through lower emotional eating.…”
Section: Optimism and Snacking Behaviormentioning
confidence: 99%
“…To our knowledge, there is no data available assessing the association between optimism and snacking behavior. Snacking has been associated with depressive symptomatology [65], perceived stress [66] and coping strategies [67]. We can hypothesize that the better coping strategies observed in more optimistic individuals [29] lead to lower psychological distress [68,69], which can in turn decrease snacking through lower emotional eating.…”
Section: Optimism and Snacking Behaviormentioning
confidence: 99%
“…It was further observed that a positive relation existed between the non-prudent dietary pattern and emotion focused coping, but again, only for individuals with the GG genotype. This positive relation between a non-prudent dietary pattern and emotion focused coping is in line with previous research (Kuczmarski et al, 2017). Again, given the possibility that the dietary pattern and genotype might produce excessive amounts of inflammation and impair cognitive flexibility, this impairment may also contribute to persistent use of emotionfocused coping strategies, as individuals who are less flexible in the use of their coping methods tend to endorse emotion-focused coping strategies to a greater degree (Gabrys, Anisman, & Matheson, 2018).…”
Section: Interactive Effects Of Genotype Sex and Dietary Patternsupporting
confidence: 87%
“…The present findings indicated that dietary patterns were not related to any of the outcome variables. This was somewhat surprising, given the abundance of past research indicating that diet may be predictive of cognition (e.g., Freeman, Haley-Zitlin, Rosenberger, & Granholm, 2014), coping (e.g., Kuczmarski et al, 2017), and depression (e.g., O'Neil et al, 2014). The present findings also revealed that both dimensions of cognitive flexibility (cognitive control and cognitive resources) were highly correlated, and that both dimensions were negatively associated with emotion-focused coping, typical and atypical depressive symptoms, and that only cognitive resources was positively correlated with problem-focused coping, which is in line with previous research (Gabrys, Anisman, & Matheson, 2018).…”
Section: Zero-order Correlationsmentioning
confidence: 99%
See 2 more Smart Citations